Awareness of obstetric fistula and its associated factors among reproductive-aged women: Demographic and health survey data from Gambia - Rabbi Tweneboah; Eugene Budu; Patience Dzigbordi Asiam; Stephen Aguadze; Franklin Acheampong (PLoS ONE, 2023)
Childbirth complications continue to remain a major problem in various settings but most rampant in underdeveloped nations, including Gambia, where poor living condition is widespread. Obstetric Fistula (OF) has been cited as one of the most common issues experienced by mothers during labor over the years. The study thus focuses on evaluating the level of awareness of this condition among Gambian women of childbearing age. Women’s Data from the recent Demographic and Health Survey (DHS) in Gambia was used for the study. A total of 11,864 women of reproductive age, who had completed cases of the variables of interest were used for the analysis. Stata version-16 was used in carrying out the analysis of this study; and Pearson Chi-square test for independence was used to examine the distribution of the awareness of fistula among Gambian women across the explanatory variables. A two model binary logistic regression was fitted to examine the association between the outcome variable and the explanatory variables. The study presented that, majority of the Gambian women (87.2%) had no knowledge about Obstetric Fistula, as they indicated to have never heard of the condition. Considering the individual factors, age was seen to be a significant factor in determining the awareness level of Obstetric Fistula among women of childbearing age. As they age, the higher their odds of knowing about the condition. Other factors such as level of education, marital status, pregnancy termination, media exposure, community poverty level, and employment were also discovered to be significant factors in determining a woman’s awareness of Obstetric Fistula. Considering the low level of awareness of Obstetric Fistula among Gambian women, there is therefore the need for the appropriate institutions to increase health educational programmes targeted at creating its awareness, and to provide further in-depth understanding of the condition to the few who already have a fair knowledge about it.